Benign tumors in gynecology and obstetrics. Benign ovarian tumors, diagnosis, and treatment clinic. - Aznaran Castillo, Francisco (2015)
45 cases of benign ovarian tumor North Central Hospital of Chiclayo, for the years 1975-1980 is reviewed.